VOCATIONAL TRAINING IN PHYSICAL EDUCATION: CRITICAL ANALYSIS OF THE PEDAGOGICAL PROJECT OF UNDERGRADUATE COURSE OF THE FEDERAL UNIVERSITY FROM AMAPÁ-BRAZIL (Fiep Bulletin - online, 2014)
The current research had as goal to analyze critically the Pedagogical Project of Undergraduate Course in Physical Education from the Federal University from Amapá-UNIFAP, through the predominant concept of vocational training; the record organization; the multidisciplinary characters and; the leading principles and the goals of the course. The obtained results from the document analysis point out to a series of limitations as: man's dual conception; excessive worry with technical knowledge about body health; a great number of subjects coming from biological/health science and without connotation to the originating knowledge of the human/social science field, earth, philosophy and art and; the body culture is not comprised as an important part of historical heritage and as study object of vocational training in Physical Education directed to several fields of professional performance.
Keywords: Vocational Training; Physical Education; Pedagogical Project